Pengaruh Leverage, Pertumbuhan Penjualan, dan Ukuran Perusahaan Terhadap Tax Avoidance - Salma Mustika Ainniyya; Ati Sumiati; Santi Susanti (Owner : Riset dan Jurnal Akuntansi, 2021)
Tax Avoidance is an act to avoid taxes by companies that can reduce tax revenue for the state. This study aims to examine the effect of Leverage, Sales Growth, and Company Size on Tax Avoidance. Population in this study were all companies listed in Indonesia Stock Exchange for 2018 – 2019 period. Purposive sampling used as sampling technique and obtained 219 companies as samples. This study used quantitative method and the analysis was multiple linear regression analysis. Tax Avoidance proxied by Effective Tax Rate which have a negative interpretation of Tax Avoidance. The result of t test shows that Leverage has a significant effect on Tax Avoidance, positive relationship between Debt to Equity Ratio as proxy for Leverage and Effective Tax Rateas proxy for Tax Avoidance explains that the higher the Leverage, the lower the Tax Avoidance. Sales Growth has a significant effect on Tax Avoidance, negative relationship between sales growth and Effective Tax Rate explains that the higher the Sales Growth, the higher the Tax Avoidance. While Company Size has no significant effect on Tax Avoidance, bigger or smaller the Company Size will not have any effect on Tax Avoidance. The f test shows that Leverage, Sales Growth, and Company Size simultaneously have a significant effect on Tax Avoidance. Result of adjusted R square shows that the effect of Leverage, Sales Growth, and Company Size on Tax Avoidance is 0,072 or 7,2%.